here is my issue

Everyone knows thats

Its assumed when beta = infinity ib = 0

Ie = (b+1)(ib)

Also

Ie = ib+ic

Hence most people say when Ib=0

Ic = ie

These two equations are contradictory.

From the first equation we see that if ib = 0 then Ie = 0

from the second equation we see that if ib = 0 then Ic = ie

How is this possible.

I know beta = infinity is commonly referred to as saturation

But i can't recall why these two equations are contradictory like this.

They must agree and for the reasons stated above they do not

Someone help me remember why please?